Utilization of rock phosphate by crops on a representative toposequence in the northern Guinea savanna zone of Nigeria: response by Mucuna pruriens, Lablab purpureus, and maize - Vanlauwe, Bernard; Nwoke, O.C.; Diels, J.; Sanginga, P.; Carsky, R.J.; Deckers, J.; Merckx, Roel (Elsevier, 2000)
The availability of P from rock phosphate (RP) is often too low to demonstrate an immediate impact on cereal production. Legumes may improve the immediate availability of P from RP and eventually benefit subsequent maize crops. The ability of Mucuna pruriens (L.) var utilis (Wright) Burck and Lablab purpureus L. to use P from RP and the changes in selected plant and symbiotic properties and in the soil available P and particulate organic matter (POM) pool as affected by the addition of RP were measured for a set of soils on a representative toposequence (‘plateau', ‘slope' and ‘valley' field) in the Northern Guinea savanna zone of Nigeria. At 18 weeks after planting (WAP), Mucuna accumulated significantly more N and P in the total biomass in the plots treated with RP compared to the plots without RP addition on all fields. Nitrogen accumulation of Mucuna reached 175, 177 and 164 kg N ha−1 in the treatments with RP on the ‘plateau', ‘slope' and ‘valley' fields, respectively. Phosphorus accumulation of Mucuna was highest at 18 WAP in all sites and reached 10, 14 and 10 kg P ha−1 in the treatments with RP on the ‘plateau', ‘slope' and ‘valley' fields, respectively. Lablab accumulated significantly more N and P at 18 WAP only on the ‘plateau' field, but some of the potential differences in N or P accumulation may have been masked by various pests especially affecting Lablab. A highly significant negative correlation was observed between the aboveground biomass at 16 WAP and the nematode population. The addition of RP significantly increased arbuscular mycorrhizal fungi (AMF) infection of the Mucuna (from 24 to 33%) and Lablab roots (from 15 to 28%) to a similar extent in all fields. This increased AMF infection was most likely caused by specific processes in the rhizosphere of the legumes as AMF infection of the maize roots (8%) was not affected by RP addition. Increases in nodule numbers and fresh weight were site- and species-specific and highest for the ‘plateau' and ‘slope' fields. The number of nodules increased on average from 8 to 19 (3 plants)−1 and from 7 to 30 (3 plants)−1 for Mucuna and Lablab, respectively, after RP addition. Although nearly all the aboveground legume biomass had disappeared from the soil surface at 51 WAP, both the Olsen-P status and POM N concentration were increased by the presence of legumes. Mucuna significantly enhanced the Olsen-P content of the soil after RP addition compared to the Lablab or maize treatments on the ‘plateau' and ‘valley' fields. Due to the relatively high initial Olsen-P content of the ‘slope' field (14 mg kg−1), differences between treatments were not significant. The N concentration of the POM pool was significantly higher under legumes than under maize on the ‘slope' and ‘valley' fields, and indicates incorporation of part of the legume biomass in the POM pool. The addition of RP to herbaceous legumes was observed to lead to site- and species-specific changes in the tripartite legume–rhizobium–mycorrhizal fungus, driven by processes taking place in the rhizosphere of the legumes, and in the soil available P pool. A cereal following these herbaceous legumes could benefit from this improvement in soil fertility status.